Respuesta :

Answer:

The answer to your question is the letter A.    (4, -8)   and  (1, -5)

Step-by-step explanation:

Data

                x + y = -4              Equation l

                y = x² - 6x             Equation ll

Process

1.- Substitute equation ll in equation l

              x + x² - 6x = -4

2.- Solve the quadratic equation

                  x² - 5x + 4 = 0

Factor        (x - 4)(x - 1) = 0

-Solve for x

                   x₁ - 4 = 0         x₂ - 1 = 0

                   x₁ = 4               x ₂ = 1

3.- Substitute x₁ and x₂ in equation l

         4 + y₁ = -4                     1 + y₂ = -4

              y₁ = -4 - 4                      y₂ = -4 - 1

              y₁ = -8                           y₂ = -5

4.- Solutions

             (4, -8)   and  (1, -5)

ACCESS MORE